2012
DOI: 10.1161/circinterventions.112.972356
|View full text |Cite
|
Sign up to set email alerts
|

B-type Natriuretic Peptide and Risk of Contrast-Induced Acute Kidney Injury in Acute ST-Segment–Elevation Myocardial Infarction

Abstract: Background-Contrast-induced acute kidney injury (CI-AKI) after percutaneous coronary intervention is associated with adverse short-and long-term outcomes. However, identification of patients at risk for CI-AKI is challenging. Using a large contemporary randomized trial database of patients with ST-segment-elevation myocardial infarction, we therefore sought to examine whether admission B-type natriuretic peptide (BNP) levels predict the development of CI-AKI. Methods and Results-A total of 979 ST-segment-eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
31
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 38 publications
7
31
1
Order By: Relevance
“…As shown in Figure 2, there was a graded decline in CV use among patients with SYNTAX score of <22, 22 to 32, and > 32. As discussed previously, 2 studies 1,21 have proposed a greater CV in patients with left compared to right coronary lesions; this association may be related to the increased absolute number of the epicardial vessels in the left compared to the right coronary system. Compared to the description of a coronary lesion by location, the SYNTAX score provides a more comprehensive assessment of lesion complexity.…”
Section: Discussionmentioning
confidence: 83%
“…As shown in Figure 2, there was a graded decline in CV use among patients with SYNTAX score of <22, 22 to 32, and > 32. As discussed previously, 2 studies 1,21 have proposed a greater CV in patients with left compared to right coronary lesions; this association may be related to the increased absolute number of the epicardial vessels in the left compared to the right coronary system. Compared to the description of a coronary lesion by location, the SYNTAX score provides a more comprehensive assessment of lesion complexity.…”
Section: Discussionmentioning
confidence: 83%
“…One recent study, 10 a substudy of the HORIZONS‐AMI trial, focused on the correlation between BNP and the risk of CIN in patients with acute ST‐segment elevation myocardial infarction (odds ratio: 1.29, 95% CI: 1.10 to 1.51; P <0.001); however, BNP and serial creatinine levels suitable for complete measurement were only available in 979 of the 3602 patients enrolled (27.2%) and were not sufficient to determine an optimal BNP cutoff concentration for the prediction of CIN. Another study indicated that preoperative BNP level is associated with postoperative acute kidney injury in high‐risk patients undergoing cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, however, left ventricular ejection fraction on admission was not available for all patients. Therefore, we examined BNP on admission, which can be regarded as an objective measure of left ventricular performance [35].…”
Section: Discussionmentioning
confidence: 99%